Historical Character as Realization of National Model of Image-Character in Russian Literature of the First Third of the 19th Century (N. A. Polevoy’s “Krakow Castle”) - E. M. Dzyuba (Научный диалог, 2018)
The features of the coverage of the issue of national identity in the domestic literary process of the first third of the 19th century are considered. The relevance of the study is determined by the problems raised. The author’s attention is focused on the analysis of N. A. Polevoy’s story “Krakow Castle” (1829). The work focuses on the methods of creating a national type of character, his role in the organization and development of the plot, the implementation of the idea of the story. The choice of the working definition of the term image-character , used in the identification of the features of the poetics of a romantic composition, is substantiated. To clarify the assessment of the historical image-character, the concept of “national artistic image of appearance” is introduced. Particular attention is paid to the analysis of the image of Suvorov, his artistic understanding by Polevoy. Typological similarity with the image of the servant in the Russian literary tradition (speech characteristic of the character, type of behaviour) is revealed. The author believes that the image of Suvorov is a measure of “Russian”: as its stable characteristics are considered “simplicity” of the character, as well as piety, loyalty to duty, wisdom. It is established that the image of events in focus of double optics - of the narrator and the historical character - allows Polevoy to create opposition “own - others”: Russian - French, Russian - Poles. Thus it is possible to identify typological national features inherent in the Russian man, but at the same time to reconstruct a generalized portrait of the Pole, typical strokes of the Frenchman. The novelty of the research is connected with the understanding of the modeling function of the historical character.